The Effect of Service Features and Ease of Mobile Banking on Customer Loyalty at PT. Regional Development Bank of South Sulawesi and West Sulawesi - M. Rezky Fitra Arfiyanto; Aris Baharuddin; Sulmiah; Andi Muhammad Rivai; Jamaluddin (Business Research and Administration Innovation, 2025)
This study aims to determine the influence of service features and convenience of Mobile Banking on customer loyalty of PT. South Sulawesi and West Sulawesi Regional Development Banks. To achieve this goal, researchers use indicators to measure these variables. The service feature variable indicators include feature completeness, feature requirements, feature interest, ease of use. Ease indicators include easy to learn, information systems, clear and easy to understand, so skilled. The indicators of customer loyalty include making repeated transactions, referring others, talking about positive things to others, showing immunity to competitors. This research uses quantitative research methods. Data collection techniques carried out are through observation, questionnaires, and documentation. The population in this study were 23,122 customers using Mobile Banking at Bank Sulselbar. The sampling technique used in this study was to use the slovin formula so that a total sample of 100 respondents was obtained. The data obtained from the research results were processed using data analysis and using the SPSS 25 application which consisted of validity and reliability tests, descriptive statistical data analysis techniques and inferential statistical analysis. The results of this study indicate that the indicators used in each variable of service features and convenience of Mobile Banking have a significant effect on customer loyalty at PT. South Sulawesi and West Sulawesi Regional Development Banks. This is proven based on the results of the t test and F test as well as the coefficient of determination test on the data that has been obtained.